Urban health and ecology: the promise of an avian biomonitoring tool. Issue 2 (16th February 2017) - Pollack, Lea; Ondrasek, Naomi R.; Calisi, Rebecca
Abstract: Urban-dwelling birds have the potential to serve as powerful biomonitors that reveal the impact of environmental change due to urbanization. Specifically, urban bird populations can be used to survey cities for factors that may pose both public and wildlife health concerns. Here, we review evidence supporting the use of avian biomonitors to identify threats associated with urbanization, including bioaccumulation of toxicants and the dysregulation of behavior and physiology by related stressors. In addition, we consider the use of birds to examine how factors in the urban environment can impact immunity against communicable pathogens. By studying the behavior, physiology, and ecology of urban bird populations, we can elucidate not only how avian populations are responding to environmental change, but also how unintended consequences of urbanization affect the well-being of human and non-human inhabitants.